STRATEGI PERSONAL BRANDING NESSIE JUDGE PADA YOUTUBE CHANNEL EPISODE NERROR - Ardi, Devina Monica; Karina, Mely Eka (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2024)
Social media is a website used to communicate and share content with other people. Platforms on Facebook, Instagram, Twitter, YouTube, and so on that offer features such as posting status, uploading photos and videos, and following other accounts. YouTube is a platform where it is possible to upload and distribute videos. YouTube has also become a well-known reality throughout the world. Many Indonesians use YouTube as a forum for building personal branding. One of the famous content creators on YouTube is Nessie Judge. The name Nessie Judge always seems to be the main attraction for fans of horror content. The YouTube channel account called Nessie Judge is an example of interesting personal branding. Through this channel, Nessie Judge provides quality and interesting content for its viewers. He presents video stories about conspiracies and horror which are very interesting to watch for fans of mystical content. This research uses Theory 8 concepts for the formation of personal branding, which uses qualitative descriptive analysis research methods. The results of this research show that the 8 concepts for forming Nessie Judge's personal branding are included, so that Nessie Judge is said to have succeeded in forming her branding on the YouTube channel, especially on the Nerror (Nessie Judge Horror) channel. KeywordsPersonal Branding, Youtube Channel, Strategy